2006
DOI: 10.1165/rcmb.2005-0443oc
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix Remodeling by Dynamic Strain in a Three-Dimensional Tissue-Engineered Human Airway Wall Model

Abstract: Airway wall remodeling is a hallmark of asthma, characterized by subepithelial thickening and extracellular matrix (ECM) remodeling. Mechanical stress due to hyperresponsive smooth muscle cells may contribute to this remodeling, but its relevance in a threedimensional environment (where the ECM plays an important role in modulating stresses felt by cells) is unclear. To characterize the effects of dynamic compression in ECM remodeling in a physiologically relevant three-dimensional environment, a tissue-engine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 52 publications
3
65
1
Order By: Relevance
“…We first sought to optimize culture conditions for epithelial ciliogenesis. Compared with our previous work (11,12), we found that the presence of calcium, ethanolamine, and phospho-ethanolamine as well as higher concentrations of retinoic acid (30 ng/ml) and bovine pituitary extract (200 g/ml) improved the extent of ciliogenesis and cilia length (Fig. 3).…”
Section: Resultscontrasting
confidence: 60%
See 4 more Smart Citations
“…We first sought to optimize culture conditions for epithelial ciliogenesis. Compared with our previous work (11,12), we found that the presence of calcium, ethanolamine, and phospho-ethanolamine as well as higher concentrations of retinoic acid (30 ng/ml) and bovine pituitary extract (200 g/ml) improved the extent of ciliogenesis and cilia length (Fig. 3).…”
Section: Resultscontrasting
confidence: 60%
“…It is likely that this increased susceptibility is at least partly caused by epithelial activation and damage and by factors including cytokines secreted by mesenchymal and inflammatory cells, which in turn cause loss of barrier function. However, asthmatic airways also experience compressive strain due to frequent brochocon- striction, and it has been demonstrated in vitro that mechanical compressive stress itself, at physiologically relevant levels, can activate the epithelium in asthmatic-like ways and induce airway wall remodeling events in the absence of inflammatory mediators (11,12,52,60,67,68).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations